A study to evaluate the effect of ultrasound treatment on nodules in multiple sclerosis patients. (4th May 2017) - Sánchez, Anna Gil; Andrade, Eugenia Lacasa; Marsal, Joan Valls; Tauste, Lourdes Assens; Mingot, Cristina González; Monge, Jorge Lecina; Puértolas, Margarita Casalilla; Calero, Nuria Sáez; Argemí, Albert Sacristán; Badia, Blanca Guiu; Moncusí, Silvia Peralta; Benito, Hugo Gonzalo; et al.
Abstract : Purpose/aim: Ultrasound has demonstrated anti-inflammatory and pain-relief benefits in several conditions such as cellulite or trauma events. We assessed the efficacy of ultrasound therapy on nodules associated with first-line treatments in multiple sclerosis patients. Materials and methods: Twenty-two multiple sclerosis patients were enrolled during 2013 and randomized to two groups: in the control group patients were treated only with a conventional gel prescribed for cellulite and nodules, while in the experimental group the gel was combined with ultrasound therapy. Patients were treated during 10 weeks and followed up for 10 additional weeks. Three nodules were assessed for each patient, measuring size, pain and redness at 0, 10 and 20 weeks. Results: We found a significant decrease in both groups in size, pain and redness across the three visits ( p < 0.0001 for size, p = 0.01 and p < 0.0001 for pain, and p = 0.0002 and p < 0.0001 for redness, respectively for the difference at visit 2 and 3 with respect to visit 1). More interestingly, we observed a greater reduction in pain and redness in the ultrasound-treated group, but the difference was only statistically significant at 10 weeks ( p = 0.01 for both pain and redness). On the third visit, no differences between control and experimental groups were detected, both achieving the same levels in measured variables. Conclusions: Both treatments are useful to improve skin reaction after first-line treatments, but ultrasound in combination with gel achieves a faster reduction in pain and redness, suggesting that ultrasound treatment might be a good analgesic for nodule management in multiple sclerosis patients.